Shuttle Effect Quantification for Redox Ionic Liquid Electrolyte Correlated to the Coulombic Efficiency of Supercapacitors. Issue 11 (11th August 2020) - Bodin, Charlotte; Sekhar Bongur, Chandra; Deschanels, Mathieu; Catrouillet, Sylvain; Le Vot, Steven; Favier, Frédéric; Fontaine, Olivier
Abstract: The use of redox‐active electrolytes is a good opportunity to increase the energy density of supercapacitors, the main limitation of this technology. The addition of redox molecules allows the storage of charge in the electrode and the electrolyte. The key to keeping the increase of charge is to avoid the shuttle effect of the redox molecule. Indeed, once the molecule is oxidized or reduced, it diffuses across the cell to react at the surface of the opposite electrode and the stored charge is lost. Is this shuttle effect however damageable for the device? This study proposes to answer this question by quantifying the shuttle effect and correlating it to the decrease of Coulombic efficiency of supercapacitors. Abstract : Shuttle trouble : The key to keep the increase of charge in the electrolyte of supercapacitors is to avoid the shuttle effect of the redox molecule. Once the molecule is oxidized or reduced, it diffuses across the cell to react at the surface of the second electrode and the charge stored is lost. But is this shuttle effect damageable for the device? This study proposes to answer this question by quantifying the number of shuttle and correlating it to the decrease of Coulombic efficiency of supercapacitors.